Hierarchically structured polymeric ionic liquids and polyvinylpyrrolidone mat-fibers fabricated by electrospinning. Issue 20 (5th May 2017) - Montolio, Silvia; Abarca, Gabriel; Porcar, Raúl; Dupont, Jairton; Burguete, María Isabel; García-Verdugo, Eduardo; Luis, Santiago V.
Abstract : Different polymeric ionic liquids/polyvinylpyrrolidone (PILs/PVP) fiber membranes were prepared by electrospinning from the corresponding polymeric blends. Abstract : Different polymeric ionic liquids/polyvinylpyrrolidone (PILs/PVP) fiber membranes were prepared by electrospinning from the corresponding polymeric blends. Supramolecular interpolymeric interactions between PILs and PVP seem to define not only the solution properties but also the final morphology and performance of the mat-fibers. The fine tuning of the counter anion and the length of the alkyl chain allows modulating both their hydrophilic/hydrophobic properties and their morphology. In this way, it was possible to obtain materials with potential applications in different fields as highlighted by the promising results obtained for oil–water separation or for the synthesis and stabilization of AuNPs.